1995
DOI: 10.1021/ma00124a037
|View full text |Cite
|
Sign up to set email alerts
|

Relaxations in Poly(di-n-alkyl and di-isoalkyl itaconates)

Abstract: A systematic study about the viscoelastic and dielectric relaxations was performed for a family of poli(di-re-alkyl and diisoalkyl itaconates): poly(dimethyl itaconate) (PDMI), poly(diethyl itaconate) (PDEI), poly(di-re-propyl itaconate) (PDPI), poly(di-re-butyl itaconate) (PDBI), poly(diisopropyl itaconate) (PDIPI), and poly(diisobutyl itaconate) (PDIBI). Three dielectric relaxation processes, labeled as , ß, and y were observed in all cases. Nevertheless, in some polymers a poor resolution of the peaks is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 4 publications
3
26
0
Order By: Relevance
“…1, have a rather sterically hindered backbone with one of the two main-chain carbons in the repeat unit bearing two side chains whose length is defined by the number of carbons, n, in each of the alkyl groups. As shown by their mechanical and dielectrical properties and by their thermal transitions in bulk [1][2][3][4][5], PDAI's exhibit a complex relaxational behavior which strongly depends on the alkyl side-chain length. Their different sub-glass and glass relaxation processes have been recently revisited by dielectric spectroscopy [6], which clearly confirms the existence of an additional low-temperature glass-transition, a L , in derivatives with six carbon atoms at least in the alkyl part.…”
Section: Introductionmentioning
confidence: 99%
“…1, have a rather sterically hindered backbone with one of the two main-chain carbons in the repeat unit bearing two side chains whose length is defined by the number of carbons, n, in each of the alkyl groups. As shown by their mechanical and dielectrical properties and by their thermal transitions in bulk [1][2][3][4][5], PDAI's exhibit a complex relaxational behavior which strongly depends on the alkyl side-chain length. Their different sub-glass and glass relaxation processes have been recently revisited by dielectric spectroscopy [6], which clearly confirms the existence of an additional low-temperature glass-transition, a L , in derivatives with six carbon atoms at least in the alkyl part.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we reported the dielectric and mechanical relaxations in poly(monoitaconates) and poly(diitaconates) 2, 3, 8–14. Poly(diitaconates) are a family of vinyl polymers obtained from the diesters of itaconic acid.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers show important changes in their properties, both in solution and the solid state 15–17. The thermal stability and dielectric and viscoelastic properties of several series of poly(itaconates) and copolymers containing itaconate units have been assessed by several researchers 8–14, 16, 18–23. In the case of poly(di‐ n ‐alkyl itaconates), there is an important increase of the steric hindrance because of the presence of two side groups per repeating unit.…”
Section: Introductionmentioning
confidence: 99%
“…Values of the activation energy for this peak in polymers 2 and 3 are 45 { 5 and 50 carbonates (PTCs). 25 Due to the fact that all the polymers exhibit { 5 Kcal/mol. As we can see, the uncertainty is higher than for g peak.…”
mentioning
confidence: 99%